“Enhancing Visual Literacy in Grades 5–7 through Interactive Multimedia in Art Lessons” - Axmedov Dilmurod Xolmamatovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the use of interactive multimedia to enhance visual literacy and artistic skills in grades 5–7 students during visual arts lessons. The study demonstrates that multimedia tools, including digital images, animations, and interactive applications, improve students’ engagement, creativity, and ability to interpret visual information. The integration of multimedia into lessons encourages independent thinking, collaboration, and the development of practical artistic competencies.